2016
DOI: 10.1002/chem.201601724
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrahydrophobic Fluorous Metal–Organic Framework Derived Recyclable Composite as a Promising Platform to Tackle Marine Oil Spills

Abstract: Derived from a strategically chosen hexafluorinated dicarboxylate linker aimed at the designed synthesis of a superhydrophobic metal-organic framework (MOF), the fluorine-rich nanospace of a water-stable MOF (UHMOF-100) exhibits excellent water-repellent features. It registered the highest water contact angle (≈176°) in the MOF domain, marking the first example of an ultrahydrophobic MOF. Various experimental and theoretical studies reinforce its distinctive water-repellent characteristics, and the conjugation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 85 publications
0
70
0
Order By: Relevance
“…The as-synthesized sample included guest H 2 O molecules in the other hydrophilic channels but the desolvated form selectively took in hydrophobic heptane guests within its CF 3 -decorated channels. Ghosh and colleagues 14 found that the desolvated form of the two-dimensional MOF, {[Cu 4 (L3) 4 …”
Section: Mofs Containing Fluorine-and Trifluoromethyl-substituted Orgmentioning
confidence: 99%
“…The as-synthesized sample included guest H 2 O molecules in the other hydrophilic channels but the desolvated form selectively took in hydrophobic heptane guests within its CF 3 -decorated channels. Ghosh and colleagues 14 found that the desolvated form of the two-dimensional MOF, {[Cu 4 (L3) 4 …”
Section: Mofs Containing Fluorine-and Trifluoromethyl-substituted Orgmentioning
confidence: 99%
“…To construct stable waterproof MOFs without the propensity to undergo degradation in the presence of moisture, a common approach is to introduce hydrophobic moieties into the framework or onto the crystal surface, either through de novo synthesis or through postsynthetic modification (PSM) . This kind of approach mainly focuses on lowering the surface free energy.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28] A great effort has been dedicated to fabricating porous materials with hierarchical porosity with a large specific surface area and being water resistant. Stable hydrophobic MOFs were prepared using hydrophobic functional (F and alkyl) organic linkers or through postsynthetic modification of MOF using hydrophobic groups; although, one cannot rely on many typical MOFs for the oil adsorption due to their microchannels.…”
mentioning
confidence: 99%